Paciente masculino de 60 años de edad con cirrosis hepática - Méndez Canales, Jennifer Lilibeth (2018)
Liver cirrhosis is the result of chronic liver damage, characterized by liver fibrosis and regeneration nodes with impaired protein and lipid metabolism. That is why the increased nutritional requirements forces the body to complement the need resulting deterioration of nutritional status. The disease has a high incidence of mortality worldwide, especially in males, on chronic alcohol consumption. This case study is based on a male patient 60 years old with liver cirrhosis associated with heavy drinking for 10 years. Including family history of diabetes mellitus type 2, severe clinical manifestations and altered laboratory analysis. Today the therapeutic goal of disease is to improve the nutritional status of the patient, providing the necessary nutrients properly and minimize complications base. The patient was assessed by anthropometric, biochemical, clinical and dietary methods, demonstrating adequate muscle composition, moderate malnutrition by hypoalbuminemia, presence of moderate to severe ascites, severe lower limb edema and increased intake of macronutrients. It managed to improve the nutritional status of the patient, preventing the onset of muscle catabolism and minimizing complications base. Thus providing a comprehensive treatment based on the correct caloric and protein intake is elemental.